6. Being Palestinian - Karma Nabulsi (For Palestine: Essays from the Tom Hurndall Memorial Lecture Group, 2023)
In this chapter I will illustrate and explain how my own identity is not based on a combination of the national particularisms that gave rise to the Palestinian people, but rather, upon the glue which keeps us together. My identity is based exclusively on the general will. In order to set out how and why it has happened that I rely upon the general will rather than traditional nationalist claims for identity, it is necessary to first present the particularism and history of the Palestinian people who are largely a refugee population. Next it will explain how the general will functions within Palestinian society, which crosses borders and host countries to express itself. It will conclude with examples of why Palestinian identity is so caught up in an essential struggle to create just institutions, especially for the protection of the rights of refugees, and why this latter issue is cast within the dual quest for liberty and democracy which – in our case as in most people’s – are intertwined.